MIGRATION TOWARD EUROPE IN THE CONTEXT OF SAMUEL HUNTINGTON’S CLASH OF CIVILIZATIONS THEORY - Malenica, Ljubiša (Politeia, 2025)
The article examines the phenomenon of mass migration of millions of people from African and Asian countries to Europe through the lens of Samuel Huntington’s theory of the clash of civilizations. The emphasis is placed on the security dimension of these processes and their potential to transform the countries of contemporary Western Europe within Huntington’s categorization of state types. The paper primarily focuses on the relationship between Western and Islamic civilizations, as defined by Huntington. The differing perceptions of migration in Eastern and Western Europe highlight Western Europe as the area most exposed to transformation driven by migration. By observing demographic trends among the indigenous European population and incoming migrant communities, along with demographic developments within Muslim countries, the article underscores the potential for the most significant Western European countries to transition from clearly defined members of Western civilization to the category of “cleft” and “torn” states. At the same time, the text also emphasizes the importance of individuals as carriers of identity, recognizing in that context a reciprocal link between the transitional processes at the state level, as formulated by Huntington, and the migratory movements and demographic trends of the migrant population. The conclusion stresses the importance of demography in Huntington’s theory of civilizations, as the demographic presence and strength ultimately determine both the borders of a state within a given civilization and the scope of the civilization itself.
Keywords: Migration; Europe; Clash of Civilizations; Samuel Huntington